Dimensions of loob can politicians be used as exemplars? - Baquiano, Marshaley J.; Dans-Lopez, Gilda (Philippine journal of psychology, 2011)
"This study explored the concept of loob and investigated how Filipinos intuitively perceived the loob of some of the country's leading political figures. The purpose was to determine the dimensions of loob and to find politicians that would best exemplify each of these dimensions."